Atypical Findings of Suspect Twin to Twin Transfusion Syndrome Quintero V: a Rare Case Report - Gusasih, Bahar Sangkur; Irianti, Setyorini; Aziz, Muhammad Alamsyah; Kurniadi, Andi (Indonesian Journal of Obstetrics and Gynecology, 2024)
Introduction: Twin-to-twin transfusion syndrome (TTTS) is a serious complication in monochorionic multiple pregnancies. Case Illustration: A-38 years old woman with G3P2AO felt 8 months pregnant and came for polyclinic control with the diagnosis of G3P2A0 gravida 34-35 weeks; Gemelli; Baby I Breech position; Baby I Polyhydramnios, IUFD; Suspected Twin Twin Transfusion Syndrome (TTTS Quintero V). However, atypical findings of TTTS are rarely found and should be taken as special notes such in this case. We will report a rare finding of TTTS in which the SDP level of the donor fetus was normal (not oligohydramnios). The suspected diagnosis of TTTS Quintero V in this case was made clinically based on the maternal-fetal ultrasound findings of a diamniotic monochorionic gemelli pregnancy with IUFD in the 2nd fetus II. However, there were non-standard findings in this case where the SDP level of the donor fetus was normal (not oligohydramnios). No other sequele complications were found in this case based on other examinations. Conclusions: Several therapies are available for TTTS including amnioreduction, laser ablation of the vascular placental anastomosis, selective feticide, and septostomy. Timing of delivery after management of singleton fetal death in the late second or early third trimester is debatable. Delivery method is determined based on obstetric indications.